Penerapan Nilai-Nilai Moral terhadap Santri di TPA - Taqi Subkhana; Nurul Malikah; Muhtarom Muhtarom (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Instilling morals in children from an early age is very important considering that in an increasingly modern era, moral education as the main factor in self-discipline has become a tool of internal control in behaving consistently in religion. It is very important to introduce religious and moral values ​​for young children as early as possible as the most basic foundation in the child's growth and development process. The aims of this research are (1) To describe the individual attitudes of each student at TPA Al - Jariyah prayer room. (2) To describe the application of moral values ​​to students at TPA prayer room at Al - Jariyah (3) To find out the obstacles in implementing these values. morale in the students of TPA AL – Jariyah and looking for a solution. This research uses qualitative methods by conducting direct interviews with religious figures and students. The data collection techniques used are through direct interviews and observation. The results of this research show that the Al – Jariyah TPA program has been implemented according to the program formulated by the KPM INSURI PONOROGO group. The application of santri moral values ​​has been practiced in the activities and process of habituation and example by teachers. The obstacles are the length of meetings, social interactions outside the TPA, including social media at home and in the student's living environment.